Treatment and Outcomes of Primary Urethra Cancer. (September 2018) - Eng, Tony Y.; Chen, Tiffany W.; Patel, Abhilasha J.; Vincent, Jill N.; Ha, Chul S.
Abstract : Background: Urethral cancer is a rare malignancy, representing <1% of all malignancies. Optimal management, due to its rarity, presents as a treatment dilemma for physicians. There is a lack of consensus regarding treatment as large randomized trials cannot be performed; thus, optimal management decisions rely on study of retrospective cases. This is a review of our institutional experience with urethral cancer treated with various treatment modalities. Methods: A retrospective chart review was performed on 31 patients treated for primary cancer of the urethra from 1958 to 2008. The patients were stratified by sex, histologic type, stage, date of diagnosis, type of treatment, and last follow-up. Early stage cases were designated as Tis-T2N0M0 and advanced cases were designated as T3-4, N+ or M+. Analysis was performed based on clinical stage, treatment modalities and outcomes. Results: Fourteen early stage cases and 17 advanced stage cases of urethral cancer were analyzed. The majority of early stage cases occurred in men (M:F=8:6) and the majority of advanced stage cases occurred in women (M:F=5:12). The most common histology was squamous cell carcinoma for both early and advanced stage cases. Surgery was the preferred modality of treatment for early stage cases (surgery used in 13 cases vs. chemo/radiotherapy used in 1 case) while for advanced cases, radiation ±chemotherapy was commonly used. Overall survival for this series was 45% at mean follow-up of 7 years. Eight of the 14 cases of early stage cancer remained disease free at last follow-up. Comparatively, only 5 of 17 with advanced cancers had no apparent disease at last follow-up. All but one of those patients were treated with combined modality therapy. Conclusions: Patients with early stage urethral cancers do well with single modality therapy, whereas patients who present with advanced cancers may benefit from combined modality therapy. More extensive study is required to recommend a particular treatment protocol. However, in this rare malignancy, institutional experiences provide the best evidence currently due to the lack of multi-institutional trials.